2016
DOI: 10.1093/humrep/dew239
|View full text |Cite
|
Sign up to set email alerts
|

Successful IVF pregnancy despite inadequate ovarian steroidogenesis due to congenital lipoid adrenal hyperplasia (CLAH): a case report

Abstract: Steroidogenic acute regulatory protein (StAR) mutations are the most frequent aetiologies of congenital lipoid adrenal hyperplasia (CLAH). Phenotypes may vary, and puberty may be absent in affected individuals. To date, only two pregnancies have been described in 46,XX CLAH patients with StAR mutations; these patients exhibited ovarian steroidogenesis along with spontaneous puberty and menarche and normal menses. The patient described here presented with CLAH caused by the homozygous (unreported, 1 bp) deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 13 publications
4
13
0
Order By: Relevance
“…In the successful pregnancies in CAH women caused by 17-hydroxylase de ciency and steroidogenic acute regulatory protein (StAR) mutations, the patients presented with primary amenorrhea and absent or incomplete sexual maturation [18,26]. The authors both reported that during their IVF treatment, endogenous estrogen level was very low but follicles grew normally after ovarian stimulation and normal embryos and pregnancies were obtained [18,26], just as our case reported. So we suggest that the disorders of gonadal steroidogenesis caused by rare forms of CAH may have little effect on the follicular growth and the developmental capacity of the oocytes.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In the successful pregnancies in CAH women caused by 17-hydroxylase de ciency and steroidogenic acute regulatory protein (StAR) mutations, the patients presented with primary amenorrhea and absent or incomplete sexual maturation [18,26]. The authors both reported that during their IVF treatment, endogenous estrogen level was very low but follicles grew normally after ovarian stimulation and normal embryos and pregnancies were obtained [18,26], just as our case reported. So we suggest that the disorders of gonadal steroidogenesis caused by rare forms of CAH may have little effect on the follicular growth and the developmental capacity of the oocytes.…”
Section: Discussionsupporting
confidence: 59%
“…As for low estradiol, previous reports showed estrogen may not play a key role in folliculogenesis and follicular development in vivo and in vitro [23,24], but gonadotrophins play a vital role in the growth and maturation of follicles [25]. In the successful pregnancies in CAH women caused by 17-hydroxylase de ciency and steroidogenic acute regulatory protein (StAR) mutations, the patients presented with primary amenorrhea and absent or incomplete sexual maturation [18,26]. The authors both reported that during their IVF treatment, endogenous estrogen level was very low but follicles grew normally after ovarian stimulation and normal embryos and pregnancies were obtained [18,26], just as our case reported.…”
Section: Discussionmentioning
confidence: 99%
“…100 In vitro fertilization and transfer of cryopreserved embryos has successfully resulted in a live birth in lipoid CAH and 17OH deficiency. 101,102 Patients with POR, StAR, and CYP17A1 mutations may also have ovarian cysts and ovarian cyst torsion. [103][104][105] In the virilizing forms of CAH, excess adrenal sex steroids can lead to hypogonadotropic hypogonadism 106,107 and increased progesterone can interfere with endometrial implantation.…”
Section: Long-term Complicationsmentioning
confidence: 99%
“…In non-classical forms of CAH due to partial enzyme deficiencies, live-birth rates are higher (63-90%) than classical CAH and are similar to age-matched controls [24]. In more rare forms of 46,XX CAH that may also affect gonadal steroid production, fertility is rarely described, other than in few case reports of a spontaneous pregnancy, e.g., in an individual with 3β-hydroxysteroid dehydrogenase deficiency [148], and successful in vitro fertilization (IVF) in individuals with 17α-hydroxylase deficiency [149][150][151], and another with congenital lipoid adrenal hyperplasia [152]. In CAH, infertility may occur as a result of anovulation, menstrual irregularities, thickening of cervical mucus, and anatomical factors [132].…”
Section: Disorders Of Androgen Production or Actionmentioning
confidence: 92%